PERAN DAN STRATEGI GURU AGAMA HINDU DALAM MEMBANGUN SIKAP JUJUR DAN DISIPLIN ANAK - I Gusti Ayoe Made Mas Reyke Tiara Putri; Ni Wayan Eka Krisnayani; Ida Bagus Kade Yoga Pramana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Character education is an important aspect in children's self-development, especially in the context of forming honest and disciplined attitudes. This journal is to identify the roles and strategies of Hindu religious teachers applied by Hindu religious teachers in building these two attitudes among students. The method used is a qualitative approach with interview and observation techniques in several schools. The research results show that Hindu religious teachers act as role models, educators and motivators. The strategies implemented include integrating religious values ​​in learning, applying discipline through daily activities, and fostering open communication between teachers, students and parents. Thus, it is hoped that teachers' active role in teaching the values ​​of honesty and discipline can shape children's positive character and prepare them to face life's challenges in the future. The analysis shows that the role of Hindu religious teachers in building honest and disciplined character includes the role of a catalyst; Teachers function more as role models by emphasizing their statements or utterances which are always based on their conscience. Students have another role as educators, talking about the sources of Hindu teachings, and guiding them through their own experiences. Another role is as a motivator, encouraging students to comply with school and class rules by providing rewards or sanctions. However, the approach used by Hindu religious teachers is to